Quality Analysis of Five Bioactive Compounds in Mentha haplocalyx Extracts by High Performance Liquid Chromatography - Jin, Yuqin; Cao, Gang; Chen, Xiaocheng; Zhu, Yongjian (Asian Journal of Chemistry, 2014)
Mentha haplocalyx is derived from the aerial part of Mentha haplocalyx Brip. Caffeic acid, hesperidin, rosmarinic acid, buddleoside and diosmetin are active constituent of Mentha haplocalyx used in many traditional Chinese medicines. This paper describes a sensitive and specific assay for the determination of five bioactive compounds in Mentha haplocalyx extracts. In this paper, the five components were separated on an Agilent Zorbax Eclipse XDB-C18 column (250 × 4.6 mm, 5 μm) and detected by diode array detector (DAD). Mobile phase was composed of (A) aqueous phosphoric acid (0.5 %, v/v) and (B) acetonitrile using a gradient elution. Analytes were performed at 30 °C with a flow rate of 1 mL/min and UV detection at 340 nm. All calibration curves showed good linear regression (r2 ³ 0.9999) within tested ranges. The LOD and LOQ were 0.31-5.93 and 2.98-57 μg/mL, respectively. Overall intra-day and inter-day variations were less than 2.19 % and th e average recoveries were 98.23-100.04 % for the analytes. This newly established method is validated as simple, precise and accurate. It can be used as a valid analytical method for intrinsic quality control of Mentha haplocalyx. In conclusion, the proposed method would be sensitive enough and reliable for comprehensive quality control for clinical use and modernization of traditional Chinese medicines.